Multicomponent chiral separations by analytical and preparative liquid chromatography - Ribeiro, António E. (2014)
This work will present a complete methodology concerning experimental, modelling and simulation results. Both the CHIRALPAK AD and CHIRALPAK IA CSP will be evaluated. The selection of the proper CSP/solvent combination for preparative operation will be fully study taking into account the screening strategy proposed by Zhang et al. Additional results include the measurement of nadolol stereoisomers solubilities, equilibrium adsorption data and fixed bed (breakthroughs) experiments. The complete screening of CSP/solvent combination will lead to the choice of the better solutions for the separation of nadolol stereoisomers, considering the target component or components to be obtained. Simulation and experimental results will be presented for the multicomponent separation of nadolol stereoisomers by multicolumn and Simulated Moving Bed adsorption processes.